A Comment on Comment Clauses: Data from European Portuguese - Cardoso, Aida (2018)
In this study, we analyze the prosodic realization of comment clauses in European Portuguese in a corpus of spontaneous speech: the Portuguese C-ORAL-ROM corpus. Focusing our analysis on comment clauses involving the verb ‘dizer’ (‘to say’), our main goal is to find if there is a pattern in the prosodic realization of similar comment clauses. Building on regular patterns found for the prosodic structure of these constructions, we discuss systematic relations between prosody and discourse structure in terms of semantic-pragmatic meaning. Our data evidences some regularities in the behaviour of comment clauses involving the verb ‘dizer’ (‘to say’), but we also found asymmetries between the prosodic realization of comment clauses constructed with different verb forms (the conditional form ‘diria’ –‘I would say’ –and the subjunctive form ‘digamos’ –‘let’s say’). We discuss these results considering three main points: (i) the results that have been described for parentheticals (and especially comment clauses) for other languages, (ii) the relation between prosodic structure and scope disambiguation, and (iii) the role of the concept of ‘cline of grammaticalization’ (Dehé & Wichmann, 2010) in the understanding of the status of comment clauses in the informational structure of the sentence.